Analysis of the thyrotropin receptor-thyrotropin interaction by comparative modeling - Núñez Miguel, Ricardo; Sanders, Jane; Jeffreys, Jennifer; Depraetere, Hilde; Evans, Michele; Richards, Tonya; Blundell, Tom L; Rees Smith, Bernard; Furmaniak, Jadwiga (Thyroid (New York, N.Y.), 2004)
We have used the most advanced programs currently available to construct the first three-domain structure of the human thyrotropin receptor (TSHR) using comparative modeling. The model consists of a leucine-rich domain (LRD; amino acids 36-281; porcine ribonuclease inhibitor used as a template for modeling), a cleavage domain (CD; amino acids 282-409; tissue inhibitor of matrix metalloproteinases 2 as template) and transmembrane domain (TMD amino acids 410-699; bovine rhodopsin as template). Models of human, porcine, and bovine TSH were also constructed (human chorionic gonadotropin [hCG] and human follicle stimulating hormone [hFSH] as templates). The LRD has a characteristic horseshoe shape with 10 tandem homologous repeats. The CD consists of beta-barrel and alpha helix structures (OB-like fold) with two disulfide bridges and the structure around these disulfide bridges remains stable after cleavage. The TMD presents the typical seven membrane-spanning helices. The TSH, LRD, CD, and TMD models were brought together in an extensive series of docking experiments. Known features of the TSH-TSHR interaction were used for selection of appropriate complexes that were then validated using a different set of experimental data. A similar approach was used to build a model of a complex between the TSHR and a monoclonal TSHR antibody with weak thyroid stimulating activity. Human thyrotropin (hTSH) alpha chains were found to make contact with many amino acids on the LRD surface and CD surface whereas no interaction between the beta chains and the CD were found. The higher affinity of bovine thyrotropin (bTSH) and porcine thyrotropin (pTSH) (relative to hTSH) for the TSHR is explained well by the models in terms of charge-charge interactions between their alpha chains and the receptor. Experimental observations showing increased sensitivity of the TSHR to hCG after mutation of TSHR Lys209 to Glu are explained well by our model. Furthermore, several mutations in the TMD that are associated with increased TSHR basal activity are predicted from our model to be caused by the formation of new interactions that stabilize the activated form of the TMD.